THE CYBERSPACE AND MILITARY MODERNIZATION: LEADERSHIP, TRAINING, AND HUMAN RESOURCE STRATEGY - Khulan Dorjpalam (International Journal of Innovative Technologies in Social Science, 2025)
This article explores cyberspace as a new strategic domain made up of interconnected networks of information technology infrastructure and analyzes the changes taking place in the management, training, and human resource policies of the armed forces. The research utilizes theoretical analysis, international experiences, and comparative research methods, focusing on case studies from NATO, the United States, Germany, the United Kingdom, Russia, China, and Estonia. It discusses the theoretical perspective of considering cyberspace as a fifth conflict domain, cyber force structure and management reform, red/blue team training, and ongoing capability development trends. The findings highlight that addressing cyberspace issues requires not only technical solutions but also a comprehensive modernization of strategy, organization, and human factors. This underscores the critical importance of developing human resource policies, management structures, and training systems in the defense sector as part of an integrated strategy. Dedicated cyber forces have improved response times to cyber incidents, while enhanced training programs have bolstered cyber discipline and threat awareness among military personnel. Effective cyber defense necessitates the development of human resource policies, management structures, and training systems within the defense sector as part of a cohesive strategy. The research emphasizes the need for a holistic ecosystem encompassing practical training, continuous capability development, flexible human resource policies, multidisciplinary expertise, and robust public-private partnerships to combat evolving cyber threats. Sustaining a competitive edge in cybersecurity requires ongoing adaptation and investment in technological infrastructure and human capital development.